Սրբադասման նախաշավիղներով. մարտիրոսների պաշտամունքի որոշ կարգավորումների առանձնահատկությունները վաղ եկեղեցում - Հարությունյան, Գառնիկ (Մատենադարան)
This article aims to examine the canonical-juridical regulations preserved in the history of the Early Church (until the 5th c.), which in one way or another refer to the various parts of the process later called canonization. Some important peculiarities concerning the regulations of the veneration of martyrs in the Early Church can be stressed; they indirectly refer to the martyrs’ canonization. Though at first the Church had no intention to officially declare (canonize) the veneration of martyrs, some regulations obviously led to the formation of the canonical process of canonization. Firstly, the term “martyr” was clarified: by that term the Christians of the first centuries persecuted for their faith were meant. A “martyr” would not seek death but at the same time he/she would not attempt to avoid death and would publicly witness to Christ. Secondly, such a Christian had to profess the orthodox faith, since the heretics persecuted for their religion could not be venerated as true martyrs (an examination into the personality of the persecuted Christian was required). The veneration of martyrs was reflected in the rituals – their names were included in the diptychs of local churches to be commemorated once a year during the Divine Liturgy. Also, believers visited their graves, and the presence of martyrs’ remnants or relics became a must for the places of their veneration (in this case too corroboration was necessary, for which the local bishop was responsible). В статье в историческом контексте рассматриваются канонические установления ранней Церкви (до V в.), которые так или иначе касаются процесса, позже получившего название канонизации. Изначально Церковь не намеревалась официально провозглашать (канонизировать) почитание мучеников; тем не менее можно отметить разные регуляции, которые постепенно привели к канонизации как церковно-правовому процессу. Во-первых, был уточнен термин “мученик”: под этим словом подразумевался христианин, преследуемый за веру. “Мученик” не искал смерти, но в то же время и не избегал ее, и публично свидетельствовал о Христе. Такой христианин должен был исповедовать православную (ортодоксальную) веру, так как еретики не считались истинными мучениками. Это предполагало некоторое расследование о личности мученика. Почитание мучеников стало оформляться в ритуал: их имена были включены в диптихи местной церкви, чтобы поминать их ежегодно в день их кончины во время литургии. Кроме того, верующие посещали места их погребения. Со временем было установлено обязательное наличие останков или мощей мученика в местах его почитания (это тоже предполагало расследование, проведение которого возлагалось на местного епископа).
Keywords: Պատմություն; Սրբադասում